A Voice of Protest in Mulk Raj Anand’s Untouchable - Irfan Ahmad Dar (The Creative Launcher, 2017)
Literature is a means whereby immediacy of the life is recreated. As a social phenomenon and highest form of development of human sensibility, it is inspired by the socio-political events of an arena. Litterateur’s take us on a journey to the world of their own creation that is the portrayal and the living document of the contemporary socio-political happenings of the societies. This implies the fact that, through their great artistic creations, they strive to bring us closer to the life and at the same time help us differentiate the real from the hyper-real and thereby shed the veil of our false ideology and preconceived mindset. Thus, literature is a mirror of life for we know writing never comes out in a vacuum rather there is always a full-fledged design behind every literary piece and every work has a proper socio-cultural, political, and economic environment. Every writer, therefore, assumes an importance of a hero for every time his pen spills ink, it is out of proper design: the design to stir the masses for something good, to question the status quo, to raise their voice against any dehumanising practice or oppression and in nutshell to righten the wrongs. People usually describe literary texts as the blueprints of the economics, family relations, environment, and attitudes. If we turn to the West, we have some prominent figures like Milton, Pope, and Wordsworth who left an indelible mark in reconstructing societies that would bear no room for the flaws. India in this connection did not lag behind. Here too we have literary figures like Raja Rao and Mulk Raj Anand who through their philosophic vision voiced some key concerns of the societies. Mulk Raj Anand’s literature is the representation of his own age. This paper is an attempt to probe into the literature of protest of Mulk Raj Anand vis a vis his prominent novel Untouchable (1935), aimed at the rejuvenating and refashioning the societies.